The Effect of Steaming Time on Microstructural Changes of Instant Noodles - Lalana Chewangkul,; Wunwiboon Garnjanagoonchorn,; Onanong Naivikul, (Agriculture and Natural Resources, 2002)
Confocal laser scanning microscopy (CLSM) was used for examining microstructural differences resulted from different steaming time in modern instant noodles production. Fresh noodles were subjected to a saturated steam tunnel for 0, 1 or 3 minutes prior to entering a 135°C fryer for 50 seconds. The obtained noodles were then rehydrated and examined by CLSM. Three microstructural parameters: degree of starch swelling, starch-protein association and protein continuity were evaluated. CLSM images showed the 3-minutes steamed samples to have a greater amount of swollen starch, better association between starch granules and protein matrix and better continuity of protein network. Thus, fundamental understanding of microscopic spatial arrangement between starch and protein affected by steaming time in instant noodles processing could be achieved via CLSM.